Empowering Activator Teacher in The Context of Educational Transformation in SMKN Kota Malang - Rini, Devi Indra; Burhanuddin, Burhanuddin; Sunandar, Asep (Universitas Negeri Malang, 2024)
Abstract: The presence of activator teachers in schools can be an agent of change in schools. The purpose of this study is to explore and identify how activator teachers can be empowered in the transformation of education in Vocational High Schools (SMK). This study used qualitative research method of exploratory case study type. The conclusion of the research shows that the transformation of education in SMKN Kota Malang is well planned so that it has a significant positive impact. By involving all stakeholders, including teachers, students, and industry. Teachers play a crucial role as agents of change in educational transformation. They act as initiators, motivators, mentors, collaboration facilitators and inspirers for other teachers. The integrated approach taken by the school in utilizing the activator teachers has proven to be effective in achieving the goals of educational transformation. By providing appropriate support, assigning additional tasks and involving them in various aspects of school management, the lead teachers can be effective agents of change in creating an adaptive, innovative and relevant learning environment. Transformation not only improves the quality of education but can also better prepare students to face future challenges. Keywords: Education transformation; activator teacher; teacher empowerment